(3QSGdI aj fSHI GdLeYs
(3ChdgG (B:s
(3hHYO, agPg QSGdI eYehdI aj fSHI GdLeY GYde Cf GdLeY dG jfSH Edjg EdG EPG de jcf dg hGMOG CUdkG cGdCYQGHj s
(3BNQgG (B:s
(3hEf CQjO Cfg dG jfSH Edjg EPG de jcf YdekG adG hLg dJNUjU GdhRf GdePchQ dg aEf GdMce aj hRf GdCfUGQ CjVkG cPdc hGddg SHMGfg hJYGdi CYde s
(3Vef eLehY s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B142 s
Keywords: (3GdfMhs